PRICKLE1 × FOCAD Interaction Revealed by Genome-Wide vQTL Analysis of Human Facial Traits - Liu, Dongjing; Ban, Hyo-Jeong; El Sergani, Ahmed M.; Lee, Myoung Keun; Hecht, Jacqueline T.; Wehby, George L.; Moreno, Lina M.; Feingold, Eleanor; Marazita, Mary L.; Cha, Seongwon; Szabo-Rogers, Heather L.; Weinberg, Seth M.; et al. (Frontiers in Genetics, 2021)
The human face is a highly complex and variable structure resulting from the intricate coordination of numerous genetic and non-genetic factors. Hundreds of genomic loci impacting quantitative facial features have been identified. While these associations have been shown to influence morphology by altering the mean size and shape of facial measures, their effect on trait variance remains unclear. We conducted a genome-wide association analysis for the variance of 20 quantitative facial measurements in 2447 European individuals and identified several suggestive variance quantitative trait loci (vQTLs). These vQTLs guided us to conduct an efficient search for gene-by-gene interactions (G × G), which uncovered an interaction between PRICKLE1 and FOCAD affecting cranial base width. We replicated this G x G interaction signal at the locus level in an additional 5128 Korean individuals. We used the hypomorphic Prickle1Beetlejuice (Prickle1Bj) mouse line to directly test the function of Prickle1 on the cranial base and observed wider cranial bases in Prickle1Bj/Bj. Importantly, we observed that the Prickle1 and Focadhesin protein colocalize in murine cranial base chondrocytes and this colocalization is abnormal in the Prickle1Bj/Bj mutants. Taken together, our findings uncovered a novel G × G effect in humans with strong support from both epidemiological and molecular studies. These results highlight the potential of studying measures of phenotypic variability in gene mapping studies of facial morphology.